A novel approach to analyze uncertainties and complexities while mapping groundwater abstractions in large irrigation schemes - Ali Nawaz, Rana; Awan, Usman Khalid; Anjum, L.; Liaqat, Umar Waqas (Elsevier, 2021)
While determining the water balance for large irrigation schemes, coping with complexities and uncertainties in estimation of groundwater (GW) abstraction is still a challenge. On other hand, estimating GW abstraction is of paramount importance to ensure the proper management of surface and GW resources. Although, there are number of well-known methods exist to map GW abstraction, utilization-factor (Uf) is considered as a reliable method. However, at large scales, tubewells utilization time required for Uf method is difficult to retrieve as large and small tubewells are governed under different rules. Geo-informatics is another emerging approach being used to estimate GW abstraction, however, there are several complexities and uncertainties involved in characterizing GW abstraction using satellite remote sensing imagery that leads to inaccurate end results. In current study, in-situ GW measurements were performed to calibrate and validate the GW abstraction estimated from geo-informatics approach at Lower Bari Doab Canal (LBDC) command area of the Indus basin of Pakistan. For in-situ measurements, an intensive tubewell survey was conducted at a grid size of 1 km at 30 locations situated at head, middle and tail end reaches of the LBDC. For the geo-informatics approach used in this study, GW abstraction is considered as a difference of actual evapotranspiration (ETa) from net canal water use and effective rainfall after satisfying soil moisture storage changes. Results of calibration of geo-informatics approach compared with the in-situ measurements showed R2 of 0.89, 0.81 and 0.79 at head, middle and tail end reaches, respectively. Intra-grid annual comparison of in-situ measurements showed that tubewells were being governed by different rules and thus yielded different abstraction within a grid ranging from 854 mm (±105) at head, 742 mm (±220) at middle and 649 mm (±244) at tail grids. Statistical analysis showed that annual GW abstraction by in-situ measurements at head 814 mm (±52), middle 769 mm (±44) and tail 688 mm (±56) end reaches varied significantly at a confidence interval of 95%. The spatial mapping by geo-informatics showed that farmers’ fields situated at proximity of head end reaches utilize 4% and 9% extra water than from those placed at middle and tail end reaches, respectively. The inequity of GW abstraction in LBDC command area highlighted in this study requires immediate intervention of policy makers for sustainable GW management.